Two-functional sensor of magnetic field and deformation based on Si<B, Ni> microcrystals - Druzhinin, A. O.; Khoverko, Yu. M.; Kutrakov, O. P.; Koretskii, R. M.; Yatsukhnenko, S. Yu. (Technology and design in electronic equipment, 2017)
This research investigates complex studies of electrical conductivity and magnetoresistance of both strain and non-strain samples of p-type Si whiskers with different degrees of doping with boron and nickel in a wide temperature range from 4.2 to 300 K. It is established that the greatest manifestation of the piezoresistive effect is observed in the vicinity of concentrations which correspond to the metal-insulator transition. Investigation of the magnetoresistance of crystals was carried out in the range of fields with induction up to 14 T. Whiskers of silicon with a doping concentration of boron of 5·1018 cm–3 can be used as a sensitive element for two-functional deformation and magnetic field sensors in difficult operating conditions.Microwires for research were grown by chemical transport reactions with the crystallographic orientation <111> and with the concentration of charge carriers, which corresponds to the vicinity of metal-insulator transition (5·1018 см–3). The nickel doping was conducted by the low-temperature diffusion from the precipitated film on the surface of the crystal. The uniaxial strain of Si microcrystals was carried out by fixing them on substrates with the different coefficient of thermal.The metallic-type temperature dependence on the resistivity is typical for heavily doped silicon microcrystals (with the bor concentration >5·1018 сm–3) for both deformed and non-deformed samples. Significant influence of the deformation on characteristics of microcrystals wasn't found. The maximum magnetoresistance of such samples doesn't exceed 4% in magnetic fields with induction of 14 T at the temperature of liquefied helium.The resistivity of Si crystals with ρ300К = 0.012 Оhm·сm (which corresponds to the dielectric side of MIT) is reduced in several times at the the temperature of liquefied helium and under the uniaxial deformation. Decreasing of boron concentration reduces this effect. This is also confirmed by the calculation of the experimental data temperature dependence of gauge factor for these samples in helium temperatures. The gauge factor is K4.2K=165 at the compressive strain ε=–5.29·10-3 RVUs. It is also found that the deformation of these samples has significant impact on characteristics of the magnetoresistance and the value of the magnetoresistance decreased almost in 3 times.The undeformed samples of Si p-type microwire doped with nickel and boron concentration in the vicinity of dielectric side to MIT can be used as the sensing element of magnetic field. The significant magnetic field dependence on magnetoresistance is observed in such crystals wich can reach a value of 250% at 14 T.